Phenomenology, Colonialism, and the Administrative State - Edward L. Rubin (Washington University Law Review, 2018)
In A Realistic Theory of Law, Brian Tamanaha rejects the claim that universal legal principles exist, and its variant that essential features of law applicable to all societies can be identified. He argues that we should define law in accordance with our society’s ordinary usage of the term and analyze law in other societies on the basis of the practices they follow on subjects that fall within the boundaries of that usage. Tamanaha then observes that the effort to identify universal principles or essential features of law has interfered with our understanding of the way that law, as we define it, has evolved over the course of human history. Even more importantly, this effort has occluded our understanding of our own legal system, which is largely organization-based and managerial, and carries out a wide variety of functions beyond the traditional one of regulating relations between private persons. There are at least two major arguments against the positions that Tamanaha advances. The argument against rejecting any universal legal standards is that this rejection is a form of cultural relativism and thus precludes our ability to make moral judgments about other nations or other societies. Are we truly willing to say that slavery or human sacrifice is not wrong, but merely reflect a different cultural perspective; are we willing to say that there are no universal principles by which we can condemn someone like Hitler? The argument against allowing all the organizational and managerial practices of our society to count as law is that it validates governmental action that violates important legal or moral principles. Are we truly willing to say that discretionary, opaque, and result-oriented behavior of modern administrative agencies does not raise concerns about their lawfulness? These may seem like separate objections, stated at different levels of generality, but I will maintain that they suffer from a common defect and thus are best answered with a single argument. That argument is that the principles by which we formulate our moral judgments are the product of our own society, the very same society that has generated our modern form of government. The idea that we can articulate and apply universal moral principles is simply a rhetorical device, characteristic of own society, and one that cannot withstand sustained examination. This does not preclude us from advancing moral arguments; rather, it means that the best moral arguments we can advance— the ones that will be most meaningful to us—are derived from our own conceptual framework, that is, the framework generated by our own society. It also means that the concepts of law and government that will be most meaningful to us are our own concepts of those institutions. We can criticize those institutions, but global condemnations of them based on different concepts, concepts that are not our own, are also little more than rhetorical devices designed to grant an illusory validity to particular criticisms being voiced within the context of our own society’s debates. The underlying theory of this argument goes beyond the boundaries of the discussion in Tamanaha’s book. The book is designed to refute certain widespread positions in Anglo-American analytic jurisprudence and does so within the framework of that jurisprudence. The basic approach of analytic jurisprudence, like analytic philosophy in general, is to interrogate our own beliefs, to demand that we reflect on the values that we hold and the consequences they imply. Tamanaha’s reliance on this approach is not a defect, because the positions against which the book is directed are probably critiqued most effectively on their own terms. In my view, there is a more philosophically and psychologically convincing way to address general questions about law and legal systems. This is Husserl’s phenomenology, an approach less common in Anglo-American jurisprudence but dominant on the European continent. I argue that phenomenology leads to a different and more effective answer to the two objections that might be raised against Tamanaha’s position, and thereby offers a different perspective on that position. Thus, it is not a critique of Tamanaha’s argument, but rather an alternative route to the same conclusions that he reaches. This article applies a phenomenological approach to the subject matter of Tamanaha’s book, and the potential criticisms against it, in four sections. Section A shows why there are no universal principles of law and why any claim to such principles is incoherent. Section B then argues that the effort to find universal principles that apply to all legal systems is an inadequate and indeed defective way to understand legal systems other than our own. Section C argues that this effort is also an inadequate and defective way to understand our own legal system. The final section then applies these arguments to the modern administrative state and shows that global critiques of it, even at the most sophisticated level, tend to be based upon such asserted universal principles. The administrative state is our society’s mode of governance; its specific features can of course be criticized, but its basic existence is the product of the same conceptual processes that generate the basis for any criticisms that we might advance.
Keywords: Phenomenology; Brian Tamanaha; A Realistic Theory of Law; Universal principles of law; Legal systems; Phenomenological approach